Assessing your strengths and weaknesses as a mountain bike racer - Bagenzer, P.
The following information is a step-by-step process by which you will be able to systematically identify your strengths and weaknesses as it relates to mountain bike racing. - Climbing - Endurance - Lactate tolernce - technical skills - Power